Aging‐Driven Composition and Distribution Changes of Electrolyte and Graphite Anode in 18650‐Type Li‐Ion Batteries (Adv. Energy Mater. 45/2022). Issue 45 (1st December 2022) - Petz, Dominik; Baran, Volodymyr; Peschel, Christoph; Winter, Martin; Nowak, Sascha; Hofmann, Michael; Kostecki, Robert; Niewa, Rainer; Bauer, Michael; Müller‐Buschbaum, Peter; Senyshyn, Anatoliy
Abstract : Lithium‐Ion Batteries In article number 2201652, Anatoliy Senyshyn and co‐workers investigate the degradation mechanisms of real life 18650‐type lithium‐ion batteries using a combination of neutron diffraction, calorimetry, infrared measurements, and chemical analytics of battery electrolytes. In addition to the increase of internal cell resistance, loss of movable lithium and "drying out" of the cell, they reveal decomposition of conducting salts to be the main driving factor in the electrolyte degradation.